Desempeño docente de las directoras con aula a cargo según percepción de los padres de familia en instituciones educativas iniciales Red N° 5 Callao - Camino Sotomayor, María Ysabel (2012)
This investigation aims to determine the level of teaching performance of the directors that are also classroom teachers at the Pre Scholar Institutions within the Callao network number 5. It was simple descriptive study. The sample consisted of 101 parents from these Pre Scholar Institutions, who have fulfilled the survey to parents to assess teaching performance of the directors that are also classroom teachers. The survey was elaborated by the author and adapted from the “Marco para la buena enseñanza de Chile”. The results revealed that parents perceive that the teacher who is also head of the institution has an excellent teaching performance.